The Effectiveness of Giving Red Ginger Water and Warm Compresses to Reduce the Intensity of Dysmenorrhoea Pain in Adolescent Girls - Wulan Dari (Indonesian Journal of Health Research and Development, 2024)
The incidence of dysmenorrhoea in the world averages 50% of women in each country experiencing dysmenorrhoea. In Indonesia, dysmenorrhoea causes adolescent girls (59.2%) to experience decreased activity, (5.6%) skip school and (35.2%) do not feel disturbed. Lampung Province in 2020 was quite high with 54.9%. Waykanan County at 88.4%. The purpose of the study was to see the effectiveness of giving red ginger water and warm compresses in reducing the intensity of dysmenorrhoea pain in adolescent girls. The implementation time is in September-October 2023 with a population of 811 people in Negeri Agung. The number of research samples was 34 samples with 2 groups. The research method uses a quasi-experimental design with a two-group pretest-posttest research design, data obtained from secondary data and primary data using Numerical Rating Scale (NRS) sheets, Univariate and Bivariate data analysis. The results showed that there was a difference in pain intensity before and after ginger water was given with a value of α 0.000 < 0.5 and there was a difference in pain intensity before and after a warm compress with a value of α 0.000 < 0.5. It can be concluded that giving ginger water and warm compresses are equally effective in overcoming dysmenorrhoea with a value of α 0.040 which means < 0.05. There was a decrease in dysmenorrhoea pain after being given red ginger water with an average of 2.36 and a decrease in dysmenorrhoea pain after being given a warm compress with an average of 2.06.